Endoscopic stenting in grade III pancreatic injury according to the American Association for the Surgery of Trauma – a systematic review of case reports and case series - Bukowski, Jan Stanisław; Marczuk, Martyna; Dziekiewicz, Marcin; Banaszkiewicz, Aleksandra (Pediatria Polska - Polish Journal of Paediatrics, 2020)
The aim of this systematic review is to summarise the evidence on the use of endoscopic ductal stenting in children with grade III pancreatic injury (according to the American Association for the Surgery of Trauma – AAST). To our review we included all patients ≤ 18 years old with endoscopic stenting due to an AAST grade III pancreatic injury from a systematic search and a retrospective chart review in our institution. In total, 34 cases of children were evaluated. In 25 cases (73.5%), the stent was placed across the duct transection site and in seven patients (20.6%) it was a transpapillary stent. Endoscopic stent insertion allowed surgery to be avoided in 79.4% of them. Pseudocysts appeared in 8/34 cases (23.5%). Endoscopic stenting appears to be a promising treatment option in the majority of children with AAST grade III pancreatic injury; more research is needed.